Perancangan Dan Pembuatan Pengamanan Video Chat Dengan Menggunakan Metode Enkripsi RC4 - Putra, Stevie Suwanto; Budhi, Gregorius Satia; Andjarwirawan, Justinus (Jurnal Infra, 2015)
Technological development at this time has been growing rapidly with the internet. Along with the development the more the usefulness of the Internet. Not only used for browsing, now the Internet is also used for communication. Such as email, chat, and etc. The increasing development of communication technology, then people start to think about the secure of the communication technology. As in a video chat, only the person entitled to know the information in the video chat. But the encryption process on existing processes such as blackbox said due to lack of transparency.Of these problems lead to the idea to make a video chat application that uses cryptographic security techniques. Data of video chat will be encrypted using RC4 method. Research shows when the data that has been encrypted can be displayed when password is correct. It shows when data that has been encrypted safer than the data that is not encrypted.